2007
DOI: 10.1128/jcm.00042-07
|View full text |Cite
|
Sign up to set email alerts
|

Virulence Gene- and Pandemic Group-Specific Marker Profiling of Clinical Vibrio parahaemolyticus Isolates

Abstract: Vibrio parahaemolyticus is a halophilic bacterium capable of causing food-and waterborne gastroenteritis, wound infections, and septicemia in humans. The organism has recently received increasing attention, as the emergence of a new clone, V. parahaemolyticus O3:K6, has resulted in the first documented pandemic spread of V. parahaemolyticus. We used microarray analyses to explore the presence of known virulence factors and genetic markers thought to be specific for V. parahaemolyticus O3:K6 and its clonal deri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
51
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(55 citation statements)
references
References 44 publications
(49 reference statements)
4
51
0
Order By: Relevance
“…The tdh genes are embedded in VPC-12. In addition, it has been reported that other putative virulence genes, including TTSS2, are encoded in VPC-12 (20). The involvement of the TTSS2 genes in the cytotoxicity and enterotoxicity of V. parahaemolyticus was demonstrated previously (15,31).…”
Section: Resultsmentioning
confidence: 92%
“…The tdh genes are embedded in VPC-12. In addition, it has been reported that other putative virulence genes, including TTSS2, are encoded in VPC-12 (20). The involvement of the TTSS2 genes in the cytotoxicity and enterotoxicity of V. parahaemolyticus was demonstrated previously (15,31).…”
Section: Resultsmentioning
confidence: 92%
“…However, PMA339 has not been observed among clinical isolates. TTSS2 genes have been found in other V. parahaemolyticus clinical strains (20); however, we identifi ed them in environmental strains. On the basis of sequences obtained from their amplicons, TTSS2 genes in PMA339 seem to have independently evolved from the pandemic strain over a considerable time.…”
Section: Discussionmentioning
confidence: 91%
“…Because the presence of TTSS2 genes is not exclusive to the pandemic strain (20) T3SS2). Among these strains, only PMA339, isolated from shellfi sh in the summer of 2004, was positive.…”
Section: T3ss2 Genes In Other Nonpandemic V Parahaemolyticus Strainsmentioning
confidence: 99%
“…These variations are a weakness inherent to PFGE as a method and not unique to the V. parahaemolyticus protocol (12,22,33). Such disparities are unlikely to be eliminated and are likely to be due to variations in equipment, different lots of laboratory supplies and reagents, and user variation, which can affect the outcome of the resulting PFGE patterns.…”
Section: Discussionmentioning
confidence: 99%
“…The organism was first identified as a cause of food-borne illness in Japan in 1950 (13). Isolates carrying one or both of the virulence factors, thermostable direct hemolysin (TDH) and the TDH-related hemolysin (TRH), are considered virulent (22,27,32).…”
mentioning
confidence: 99%